2022
DOI: 10.1101/2022.12.18.520950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-Injury Mechanoreceptor Ablation Reduces Nociceptor-Driven Spinal Cord Injury-Induced Neuropathic Pain

Abstract: Evidence from previous studies supports the concept that spinal cord injury (SCI) induced neuropathic pain (NP) has its neural roots in the peripheral nervous system. There is uncertainty about how and to which degree nociceptors and mechanoreceptors contribute. Sensorimotor activation-based interventions (e.g. treadmill training) have been shown to reduce NP following experimental SCI, suggesting transmission of pain-alleviating signals through mechanoreceptors. At the same time, nociceptors have been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The enlargement of DRG in individuals with SCI and BLP suggests that changes at the level of the junction between PNS and CNS are of relevance for the development of neuropathic pain below the level of injury. This assumption of direct PNS involvement in BLP is supported by recent studies that revealed neuronal nociceptive hyperexcitability after SCI in animal models [11, 36]. An association between pain and structural changes of the sciatic nerve could not be found for MRN parameters of the sciatic nerve in our cohort, which may be due to the fact that it is not yet possible to discriminate between sensory and motor fiber lesions in mixed peripheral nerves using MRN.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The enlargement of DRG in individuals with SCI and BLP suggests that changes at the level of the junction between PNS and CNS are of relevance for the development of neuropathic pain below the level of injury. This assumption of direct PNS involvement in BLP is supported by recent studies that revealed neuronal nociceptive hyperexcitability after SCI in animal models [11, 36]. An association between pain and structural changes of the sciatic nerve could not be found for MRN parameters of the sciatic nerve in our cohort, which may be due to the fact that it is not yet possible to discriminate between sensory and motor fiber lesions in mixed peripheral nerves using MRN.…”
Section: Discussionsupporting
confidence: 84%
“…The enlargement of DRG in individuals with SCI and BLP suggests that changes at the level of the junction between PNS and CNS are of relevance for the development of neuropathic pain below the level of injury. This assumption of direct PNS involvement in BLP is supported by recent studies that revealed neuronal nociceptive hyperexcitability after SCI in animal models [11,36].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation